Field Massage as a Complementary Therapy to Phototherapy in Neonates with Hyperbilirubinemia - Rizki Amelia; Motik, Rachmawati Putri; Hendra, Hendra; Supriadi, Supriadi; Pramono, Joko Sapto; Jasmawati, Jasmawati; Syukur, Nursari Abdul; Raihana, Siti; Ratna Wati; Putri, Rosalin Ariefah; Cholsakhon, Panyada (Ahmar Metastasis Health Journal, 2025)
Hyperbilirubinemia is a common neonatal condition requiring prompt treatment to prevent complications. While phototherapy is the standard approach, it has limitations and potential side effects, such as diarrhea, dehydration, skin rashes, retinal damage, hyperthermia, extended hospital stays, maternal-infant separation, and disruptions in breastfeeding. This study aimed to evaluate the effectiveness of Field massage as a complementary therapy to phototherapy in reducing serum bilirubin levels in neonates. Field massage is a gentle manipulation technique performed on the face, chest, abdomen, limbs, and neck to stimulate the vagus nerve and enhance metabolic processes, which is believed to help lower serum bilirubin levels and has shown no negative side effects. This research method used a quasi-experimental study conducted at Abdoel Wahab Sjahranie Hospital from March to June 2024 involving 20 neonates divided into two groups: a treatment group that received Field massage and phototherapy (n = 10) and a control group that only received phototherapy (n = 10). Field massage was administered twice daily at 07:00 and 16:00 for 15–20 minutes, at least one hour after feeding. Statistical analysis was conducted using the Paired T-Test to assess changes in bilirubin levels before and after treatment, while the Independent T-Test was used to compare outcomes between the treatment and control groups. The results of the study showed serum bilirubin levels decreased significantly in both groups, with a greater reduction observed in the treatment group (15.28 ± 3.01 mg/dL to 7.09 ± 1.60 mg/dL, p = 0.000) compared to the control group (15.94 ± 2.88 mg/dL to 8.63 ± 1.57 mg/dL, p = 0.000). Post-intervention analysis confirmed the superior efficacy of the combined therapy (p = 0.043). These results suggest that combining field massage with phototherapy is more effective in reducing bilirubin levels than is phototherapy alone. It was concluded that Field massage enhances phototherapy’s effectiveness in managing neonatal hyperbilirubinemia. Future research should include larger samples and explore additional therapies to reduce bilirubin. Examining phototherapy duration, hospitalization length, and bowel movement frequency could provide deeper insights.